The Effect Of The Summarization And Grouping Strategy Using The Letter (T) On First-Year Middle School Female Students In Biology And Their Associative Thinking (Journal of the College of Basic Education, 2025)
of the research: The research aims to identify the effect of the strategy of summarizing and grouping using the letter (T) on first-year middle school students in biology and their associative thinking. The researcher used the experimental design with partial control for two independent groups, one experimental and the other a control group with a post-test for associative thinking. The research sample was randomly selected from first-year middle school students from (Al-Rashid Girls Secondary School). The number of students in the research sample was (74) students, with (36) students in the experimental group studying according to the strategy of summarizing and grouping using the letter (T) and (38) students in the control group studying according to the usual method. The researcher conducted statistical equivalence between the two research groups with variables (chronological age, previous information test, previous achievement, Raven's intelligence test, associative thinking test). The researcher also specified the scientific material represented by: (Unit One: Biology and Technology, which includes: (Chapter One: Microscopes), and Chapter Two: Scientists who contributed to the development of Earth Science). As for the second unit: Building the body of a living organism It includes: (Chapter Three: The Cell), (Chapter Four: Cell Division), and (Chapter Five: Regulating the Work of Living Organisms), scheduled to be taught for the academic year (2024-2025) AD. The researcher formulated (150) behavioral objectives, and prepared the research tool represented by the associative thinking test. The validity of the tool was verified. After the researcher completed the application of the experiment, the tool was applied to the two research groups and the students' answers were corrected and processed statistically using the statistical package SPSS. The results showed that the students of the experimental group outperformed the students of the control group. In light of the results, the researcher made a number of recommendations and suggestions that were mentioned in Chapter Four.